Joseph Renard florist and grocery store on the corner of South Main Street and Fish Alley. - Unknown (Forsyth County Public Library, 2008)
No date.
Joseph Renard florist and grocery store on the corner of South Main Street and Fish Alley. The store was in business in the 1870s and 1880s.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Digital Forsyth; Forsyth County (N.C.) -- History -- Sources